The Effectiveness of Education for Environmental Sustainable Development to Enhance Environmental Literacy in Science Education: A Case Study of Hydropower - Wilujeng, I.; Dwandaru, W. S. B.; A. Rauf, R. A. Binti (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Renewable energy sources in Indonesia, such as hydropower, are very abundant. However, the utilization of these sources as alternative energy in Indonesia has not been optimized. Education for Environmental Sustainable Development (EESD) approach could be implemented in science education to give students valuable insights into the environment. The form of teaching materials for EESD is the student worksheet. The objective of this study was to analyze the effectiveness of learning using EESD-based student worksheets to improve environmental literacy. This study belonged to the quasi-experiment, and the sample was taken using a cluster sampling technique class. The findings of this research showed that the mean score of the experimental class was greater than the control class, and there was a remarkable difference in environmental literacy between the experimental and control class. Therefore, we could conclude that EESD-based student worksheets are useful to improve students’ environmental literacy.